2020
DOI: 10.1002/anie.202000860
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Enantioselective Sonogashira Type Coupling of Alkynes with α‐Bromoamides

Abstract: An asymmetric copper-catalyzed Sonogashira type coupling between alkynes and a-bromoamides has been developed. This method represents a facile approach to synthetically useful b, g-alkynyl amides from two readily available starting materials in a highly enantioselective manner. A Bisoxazoline diphenylanaline (BOPA) serves as the effective chiral ligand. Preliminary mechanistic studies support the formation of alkyl radical species. Scheme 1. The synthesis of a-alkynyl carbonyl compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…First, the stable phenylethynyl-Cu(I) reagent 7a was synthesized according to the literature. 25 Then, a series of controlled experiments were designed to check its reactivity with indole in the absence/presence of Pd(OAc) 2 and/or Sc(OTf) 3 . As shown in Table S5, (1)when using 7a as the substrate to react directly with indole in HOAc, no product was detected (Table S5, entry 1), indicating that nucleophilic addition of indole to the phenylethynyl-Cu(I) moiety is not accessible; (2) adding Pd(OAc) 2 as the catalyst to this reaction provided 5% yield of 6aa as a homocoupling product with bulky palladium black formation (Table S5, entry 2), which may proceed through transmetallation of the phenylethynyl-Cu(I) with Pd(II) to generate the phenylethynyl-Pd(II) intermediate, followed by the homocoupling reaction to give 6aa as the product; however, no indole addition product 3aa was observed, indicating that the nucleophilic addition of indole to a nucleophilic phenylethynyl-Pd(II) moiety is not accessible; (3) In the absence of indole, reaction of phenylethynyl-Cu(I) with Pd(OAc) 2 also provided only 7% yield of 6aa as the homocoupling product (Table S5, entry 4); (4) using Sc(OTf) 3 alone as the catalyst provided 8% yield of 3aa as the indole addition product, which may be explained as a Lewis acid-catalyzed indole addition reaction under the reaction conditions (Table S5, entry 3); and (5) Remarkably, using Pd(OAc) 2 /Sc(OTf) 3 as the catalyst provided 36% yield of 3aa with 8% yield of 6aa product (Table S5, entry 5), in which the yield of the indole addition product 3aa was much higher than that when using Sc(OTf) 3 alone as the catalyst, which cannot be explained as a Sc 3+ -catalyzed indole addition.…”
Section: Resultsmentioning
confidence: 99%
“…First, the stable phenylethynyl-Cu(I) reagent 7a was synthesized according to the literature. 25 Then, a series of controlled experiments were designed to check its reactivity with indole in the absence/presence of Pd(OAc) 2 and/or Sc(OTf) 3 . As shown in Table S5, (1)when using 7a as the substrate to react directly with indole in HOAc, no product was detected (Table S5, entry 1), indicating that nucleophilic addition of indole to the phenylethynyl-Cu(I) moiety is not accessible; (2) adding Pd(OAc) 2 as the catalyst to this reaction provided 5% yield of 6aa as a homocoupling product with bulky palladium black formation (Table S5, entry 2), which may proceed through transmetallation of the phenylethynyl-Cu(I) with Pd(II) to generate the phenylethynyl-Pd(II) intermediate, followed by the homocoupling reaction to give 6aa as the product; however, no indole addition product 3aa was observed, indicating that the nucleophilic addition of indole to a nucleophilic phenylethynyl-Pd(II) moiety is not accessible; (3) In the absence of indole, reaction of phenylethynyl-Cu(I) with Pd(OAc) 2 also provided only 7% yield of 6aa as the homocoupling product (Table S5, entry 4); (4) using Sc(OTf) 3 alone as the catalyst provided 8% yield of 3aa as the indole addition product, which may be explained as a Lewis acid-catalyzed indole addition reaction under the reaction conditions (Table S5, entry 3); and (5) Remarkably, using Pd(OAc) 2 /Sc(OTf) 3 as the catalyst provided 36% yield of 3aa with 8% yield of 6aa product (Table S5, entry 5), in which the yield of the indole addition product 3aa was much higher than that when using Sc(OTf) 3 alone as the catalyst, which cannot be explained as a Sc 3+ -catalyzed indole addition.…”
Section: Resultsmentioning
confidence: 99%
“…Adding TEMPO as a radical scavenger to a mixture of 1 a and 2 a led to the amount of product 1 c decreasing, with TEMPO‐trapped adduct 20 isolated in 59 % yield (Scheme 5 a). The use of a presynthesized copper acetylide 21 [13f] as the catalyst for the reaction of substrates 1 a and 2 a led to product 3 aa being formed in excellent yield under irradiation with blue LEDs, thus indicating that it is a visible intermediate in the catalytic cycle (Scheme 5 b). Using a stoichiometric amount of complex 21 with the terpyridine ligand L1 led to the formation of by‐product 22 by dimerization of 2 a .…”
Section: Figurementioning
confidence: 99%
“…In addition, Zhang's group reported an attractive Cucatalyzed enantioselective Sonogashira-type coupling between alkynes and racemic α-bromoamides (Scheme 36). 53 After extensive screening of ligands and reaction conditions, it was found that the use of iPr-BOPA promoted the model reaction with high enantioselectivity at −10 °C in MeCN. The authors demonstrated a wide substrate scope with alkyl-or arylsubstituted alkynes (electron-rich and electron-poor) as well as various bromoamides bearing alkyl, aryl, and heteroaryl groups (32 examples).…”
Section: ■ Recent Reports On Ni-catalyzed Reactionsmentioning
confidence: 99%